(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The objective of this paper is twofold. First, it wishesto examine and compare the place foreign policy takes in the constitutionalframework of two federal polities, namely the European Union and Canada. Second,it wishes to come to a fuller understanding of the meaning of the concept of’federalism’ as a means to reconcile consistency with subsidiarity in thecontext of internally divided polities. To achieve these objectives, this study proceeds byexploring the ways in which the principle of conferred powers (in thefollowing: conferral) manifests itself in the field of foreign policy in bothpolities. After having framed the question of foreign policy competence in itswider international and constitutional context, this paper first looks at thetheoretical foundations of the principle of attributed powers. Next, itexamines the mechanisms through which the principle of conferral is put intopractice. Apart from the straightforward application of the principle, thispaper also examines the correction mechanisms developed in both polities. Afterhaving collected the necessary ’raw materials’, it then proceeds to an explicitcomparative analysis.